Polisi Syariah: Keamanan untuk Siapa? - Haryanto Haryanto (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This paper is about community policing under Islamic Shari’a and its position in human security. This paper is intended to explain the characteristics and security paradigm in case Wilayatul Hisbah (Shari’a Police) in the province of Aceh. This paper connects the Shari’a police presence to human security, as well as how the characteristics of the security actors associated with maintaining order in the society of Aceh (community policing) are. As a result, the security paradigm in Aceh province is deﬁ ned as the locality value, contradictory to those oﬀ ered in the human security - to be adopted in a democratic transition regime as in Indonesia.